Utilization of Instagram @posaja_sragen for Marketing Communication to Promote PT Pos Indonesia Sragen Products - Ardiana, Ellen Ira; Suryono, Joko; Gama, Betty; Setyo, Bono (Revenue Journal: Management and Entrepreneurship, 2024)
Instagram is one of the social media most frequently accessed by internet users, so PT Pos Indonesia Sragen Branch, which operates in the expedition and financial services sector, uses Instagram as a marketing communications platform to introduce products and services to increase company sales. This research aims to identify and describe the use of social media Instagram @posaja_sragen as a marketing communication medium in introducing the products and services of PT Pos Indonesia Sragen Branch based on the marketing communication mix theory of Philip Kotler and Keller. This research focuses on the main problem faced by companies, namely the lack of public awareness regarding the products and services offered due to the limitations of conventional promotional media. The approach used in this research is qualitative with descriptive methods. Data collection techniques include observation, in-depth interviews with 10 employees and 15 customers, as well as documentation over three months. Data analysis was carried out through data reduction, data presentation, and conclusion, with data validity and reliability maintained through triangulation of sources and methods. The research results show that PT Pos Indonesia Sragen Branch has made optimal use of Instagram features, such as feeds, captions, Instagram stories, reels, hashtags, and direct messages (DMs) to introduce products and services. For example, using reels to show a fast and safe delivery process, as well as stories to promote discounts on delivery services. This strategy has proven effective in increasing engagement and interaction with customers, which is reflected in an increase in the number of followers by 25% and interactions on each post by 30%. The main benefits of using Instagram as a marketing communications medium include reducing promotional costs, ease of introducing service products, expanding communication facilities with the target market, and increasing company sales. This research concludes that the use of Instagram by PT Pos Indonesia Sragen Branch as a marketing communications medium has had a significant positive impact. As a recommendation, other companies are advised to adopt similar strategies with adjustments to suit their specific needs to maximize the potential of social media in their marketing strategies.